2019
DOI: 10.1111/ecot.12229
|View full text |Cite
|
Sign up to set email alerts
|

The effects of corruption on the human capital accumulation process: Evidence from Vietnam

Abstract: This study aims to identify the effects of corruption on the human capital accumulation process in Vietnamese provinces/cities. I employ labour quality assessments of firms as a proxy for human capital and divide human capital accumulation into the following two processes: an educational process and a process through which educational outcomes and worker training transform into labour quality. The estimation results have some notable implications for the Vietnamese context. Corruption has both negative and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…In other words, our results infer when senior management spends more time on regulation and the firm is subjected to higher bribe requests, then the manager's experience becomes an insignificant factor in firm performance. This finding is in line with the literature highlighting the fact that the effect of human capital on performance is less effective in more corrupt environments (see e.g., Ehrlich and Lui 1999;Boikos 2016;Feldmann 2017;Hoa 2020). Even though spending more time with regulation increases firm performance, the manager's experience is not significant for firm performance in the high regulation regime.…”
Section: Baseline Estimationssupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, our results infer when senior management spends more time on regulation and the firm is subjected to higher bribe requests, then the manager's experience becomes an insignificant factor in firm performance. This finding is in line with the literature highlighting the fact that the effect of human capital on performance is less effective in more corrupt environments (see e.g., Ehrlich and Lui 1999;Boikos 2016;Feldmann 2017;Hoa 2020). Even though spending more time with regulation increases firm performance, the manager's experience is not significant for firm performance in the high regulation regime.…”
Section: Baseline Estimationssupporting
confidence: 88%
“…It has been found that human capital (manager experience) is also an essential factor for firm performance (see e.g., Peni 2014;Staniewski 2016;Wu 2019). However, the effect of human capital on performance is less effective in more corrupt environments (see e.g., Ehrlich and Lui 1999;Boikos 2016;Feldmann 2017;Hoa 2020). Ehrlich and Lui (1999) argue that individuals invest more in political capital rather than human capital to improve their negotiation and bureaucratic power in corrupt environments.…”
Section: Hypothesismentioning
confidence: 99%
“…(2020), El Jabri and El Khider (2020) and Belkhatab (2022) on larger samples of countries. The same applies to Hao (2019) and El Khider and Elmaataoui (2021), who will rely on the fixed-effects method and the Autoregressive Distributed Shift method respectively.…”
Section: Empirical Analysismentioning
confidence: 99%
“…For instance, Nguyen et al (2017) revealed that the standard of primary education in Vietnam is adversely impacted by corruption. Furthermore, human capital could be poorly developed because of corruption in Vietnam (Hoa, 2019). With a focus on 185 countries, Achim (2017) supported the argument that the push for improved human capital is inhibited by corruption across countries.…”
Section: Literature Reviewmentioning
confidence: 99%